Regulatory dendritic cells: profiling, targeting, and therapeutic application. Issue 5 (October 2018) - Thomson, Angus W.; Ezzelarab, Mohamed B.
Abstract : Purpose of review: There is currently increased focus on improved understanding of how dendritic cell tolerogenicity is determined and maintained, and on their therapeutic potential. We review recent progress in profiling of regulatory dendritic cells (DCreg), innovative approaches to enhancing dendritic cell tolerogenicity in situ, ex-vivo generation of DCreg and initial clinical testing of these cells in organ transplantation. Recent findings: "Omics" studies indicate that the distinctive properties of DCreg are the result of a specific transcriptional program characterized by activation of tolerance-enhancing genes, rather than the retention of an immature state. In situ dendritic cell-directed targeting of nanovesicles bearing immune regulatory molecules can trigger in-vivo expansion of Ag-specific regulatory cells. Innovative approaches to ex-vivo modification of dendritic cells to enhance their regulatory function and capacity to migrate to secondary lymphoid organs has been described. Cross-dressing (with donor major histocompatibility complex molecules) of graft-infiltrating host dendritic cells that regulate antidonor T-cell responses has been implicated in "spontaneous" liver transplant tolerance. Clinical trials of DCreg therapy have begun in living donor renal and liver transplantation. Summary: Further definition of molecules that can be targeted to promote the function and stability of DCreg in vivo may lead to standardization of DCreg manufacturing for therapeutic application.